Enhancing Students Creativity through Design-Based Learning (DBL) in Islamic Religious Education (IRE) Study Program - Sufirmansyah, Sufirmansyah (LP. Ma'arif Janggan Magetan, 2025)
This article aims to explore the use of design-based learning (DBL) as well as measure its impact on the creativity of Islamic Religious Education (IRE) study program students. Creativity is one of the 21st century competencies that is believed to act as a catalyst for the development of other competencies such as character, citizenship, critical thinking, collaboration, and communication. This article is written based on research at IAIN Kediri, especially in the IRE study program. A mixed method with a convergent design was chosen to guide the operationalization of this research. Qualitative data were collected through interviews, observations, and documentation on the implementation of DBL in IRE Learning Innovation lectures. Meanwhile, quantitative-descriptive data based on product assessment was maximized to categorize student creativity after the implementation of DBL. Student creativity is measured by divergent thinking, originality of ideas, perseverance, and intellectual risk-taking. This article concludes that DBL is implemented with several steps such as providing assignments, setting criteria, completing challenges, and evaluating innovative products. The application of DBL has implications for student creativity, where 53,03% of students are in the very creative category, 30,3% of students are in the creative category. There are still 16,67% of students who are in the average category, but that is more due to the limited ability of students to access digital resources.